EVOLUTION OF SOVEREIGNTY: THE PROBLEM FIEID - Гайко, О.С. (The Journal of V.N. Karazin Kharkiv National University. Series "Issues of Political Science", 2012)
This article analyzes the evolution of sovereignty in Modern. Special attention is paid to the mechanisms of formation of legitimacy in the modern European states and to the establishment of control over territory and population, to the relationship between sovereignty, politics and law. The relationship between national sovereignty and the rights of citizens in a historical perspective is examined, and the major contradictions in the theory of sovereignty are discussed.